Mitigating Sexual Violence in Early Childhood through Information Service and Group Guidance to Parent - Ahmad, Raja Rahima Munawarah Raja; Diniaty, Amirah; Purnama, Raden Deceu Berlian; Riswani, Riswani; Hasgimianti, Hasgimianti; Habibah, Suci (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Sexual violence in early childhood continues to increase and is a phenomenon that hurts the Indonesian generation. Sexual violence experienced in early childhood has a serious impact on their growth and development, such as physical damage, trauma, stress, depression to loss of opportunities to continue life because they are victims of murder. Community Service (PKM) aims to mitigate through information services and Group Guidance to improve the skills of early childhood children to avoid sexual violence through parents. The target group is mothers who have early childhood. PKM activities are carried out through planning, implementation, and evaluation. Planning includes need assessment activities at the service location, including surveying the place of activity, coordinating with community leaders, namely RW and RT, and managing administration up to the RT level. Implementation activities start from perception, providing information services on mitigating sexual violence against early childhood, and conducting Group Guidance to explore the problems of target groups. The last activity is to conduct qualitative evaluations and conclude results thematically. The results of the final interview showed that the target group was satisfied because the service material was by the problems and anxieties they experienced. Target groups reveal the information provided is very useful in preventing their children from sexually violent behavior both from outside and from the family environment.